Skin conductance reveals the early development of the unconscious processing of emotions. (November 2016) - Nava, Elena; Romano, Daniele; Grassi, Massimo; Turati, Chiara
Abstract: The ability to rapidly distinguish between positive and negative facial expressions of emotions is critical for adaptive social behaviour. Increasing evidence has shown that emotions can be processed even at an unconscious level in adults. Yet, very little is still known about the early ontogeny of the unconscious processing of emotional signals conveyed by faces. Here, we investigated the processing of subliminally presented face emotional stimuli in infants as young as 3–4 months of age and sought to clarify its neural underpinnings by exploring the role of the autonomic nervous system. Using a visual preference paradigm, Experiment 1 determined the visibility threshold for happy and angry faces and established that infants detected both happy and angry faces at 200- but not at 100 msec. By measuring skin conductance response (SCR), Experiment 2 showed that the autonomic nervous system of infants reacted to both subliminally (100 msec) and supraliminally (200 msec) presented face expressions of emotions, and that SCR were higher for angry than happy facial expressions. Results revealed that 3–4 month-old infants respond to positive and negative emotions even at an unconscious level, but also show that angry faces possess an intrinsic alerting characteristics, suggestive of an adaptive meaning of the physiological response. Findings are discussed in terms of subcortical learning of emotions, and the possibility that the amygdala may be involved in such process.